2006
DOI: 10.1159/000093817
|View full text |Cite
|
Sign up to set email alerts
|

Association of Weather Conditions with Childhood Admissions for Wheezy Bronchitis or Asthma in Athens

Abstract: Background: The association between asthma morbidity and meteorological conditions is well documented, but it is not clear to what extent more specific meteorological variables are implicated. Objectives: This study was aiming to investigate whether there is any association between specific meteorological conditions and the seasonal variation and the rate of asthma admissions among children in Athens. Methods: Data were obtained retrospectively from hospital registries of the three main Children’s Hospitals in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 74 publications
(69 reference statements)
1
23
1
1
Order By: Relevance
“…Monthly CAA rates, after adjusting for paediatric beds that are not accounted for (approximately 20-22% of total number), were expressed per 10 5 populations aged the same as the studied groups. The estimation of the population for each year of the study period was based upon the 1981 and 1991 national census (10).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Monthly CAA rates, after adjusting for paediatric beds that are not accounted for (approximately 20-22% of total number), were expressed per 10 5 populations aged the same as the studied groups. The estimation of the population for each year of the study period was based upon the 1981 and 1991 national census (10).…”
Section: Methodsmentioning
confidence: 99%
“…On the contrary, weather types characterized by high air temperature, high absolute humidity, high total solar radiation and sunshine, are related to low CAA. Besides, a constant seasonal variability in asthma admissions among children in Athens was found, whereas the more implicated meteorological variables for younger asthmatic children were relative humidity and atmospheric pressure (10).…”
Section: Introductionmentioning
confidence: 90%
“…Although environmental and genetic susceptibility to allergic diseases may be important [11,12], large geographical variations in disease prevalence between peoples of similar genetic background and the trend to increasing incidence rates of allergic diseases worldwide may not be fully explained by these factors [13]. The overwhelming majority of what is known about the increasing prevalence of asthma and other allergic diseases are results from studies carried out in Western countries, whereas from Arabian Gulf countries, such as the United Arab Emirates (UAE), data are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that this cannot be explained by genetic factors and improvements in diagnostic methods alone, but environmental factors including indoor housing factors contribute to the increase. Many studies have associated environmental factors with increasing prevalence of respiratory symptoms in children [4,5,6], yet few studies have been performed in China, where most people live in concrete apartment buildings. Water and heat are supplied by district heating systems, and coal or coal gas is used for cooking.…”
Section: Introductionmentioning
confidence: 99%